Key Success Factors in Community - based Tourism: A Case Study of Koh Lone, Phuket - Chorpaka Buakaew (Prince of Songkla University, 2023)
Thesis (M.B.A., Hospitality and Tourism Management (International Program))--Prince of Songkla University, 2018